LAS0811: From Combinatorial Chemistry to Activation of Antioxidant Response Element. (24th September 2009) - Zhu, Ming; Baek, Hyounggee; Liu, Ruiwu; Song, Aimin; Lam, Kit; Lau, Derick
Abstract : The antioxidant response element (ARE) and its transcription factor, nuclear factor-erythroid 2 p45-related factor 2 (Nrf2), are potential targets for cancer chemoprevention. We sought to screen small molecules synthesized with combinatorial chemistry for activation of ARE. By high-throughput screening of 9400 small molecules from 10 combinatorial chemical libraries using HepG2 cells with an ARE-driven reporter, we have identified a novel small molecule, 1, 2-dimethoxy-4, 5-dinitrobenzene (LAS0811), as an activator of the ARE. LAS0811 upregulated the activity of NAD(P)H:quinone oxidoreductase 1 (NQO1), a representative antioxidative enzyme regulated by ARE. It enhanced production of an endogenous reducing agent, glutathione (GSH). In addition, LAS0811 induced expression of heme oxygenase 1 (HO1), which is an ARE-regulated enzyme with anti-inflammatory activity. Furthermore, LAS0811 reduced cell death due to the cytotoxic stress of a strong oxidant, t-butyl hydroperoxide (t-BOOH). Mechanistically, LAS0811 upregulated the expression of Nrf2 and promoted its translocation into the nuclei leading to subsequent ARE activation. Taken together, LAS0811 is a novel activator of the ARE and its associated detoxifying genes and, thus, a potential agent for cancer chemoprevention.